Ironical Excursus - Bagina, Elena (project baikal, 2017)
In the late 19th – early 21st centuries architecture experienced revolutionary changes. Professional paradigms changed several times. Inside those paradigms, there was a formation of different comprehensions of goals and tasks of architecture, of necessary professional knowledge and skills, and of a new framework of categories and concepts. The vision of an architectural form changed correspondingly. The nature of a professional also changed.